A review on perovskite solar cells: Evolution of architecture, fabrication techniques, commercialization issues and status. (1st March 2020) - Roy, Priyanka; Kumar Sinha, Numeshwar; Tiwari, Sanjay; Khare, Ayush
Highlights: Discussion on why the material perovskite is an ideal choice of researchers these days. The details on progress in efficiency and stability within a decade. Device architectures and fabrication techniques for laboratory and large scale purpose. Factors responsible for rapid degradation in PSCs along with the issue of toxicity. Commercialization status update. Abstract: Perovskite Solar Cells (PSCs) have grabbed the attention of the researchers worldwide owing to their outstanding Photovoltaic (PV) performance. PSCs are the future of the PV technology as they are capable of generating power with performance being comparable with the leading Silicon solar cells, with the cost being lower than Silicon solar cells. The enormous potential of PSCs is evident from the fact that the efficiency of these cells has risen from 3.8% to 25.2% within a decade, and it is continuously rising to date. We discuss the features making PSCs superior to contemporary PV technologies. The description of the evolution of efficiency and various architectures used to date has been presented. The perovskite film fabrication techniques with some large scale perovskite solar cell manufacturing techniques are discussed. Despite positive traits, the PSCs have faced some issues, such as degradation in the presence of moisture, oxygen, and UV, toxicity, etc. The impact of these factors with various remedies adopted by researchers has been discussed. However, the instability issue raised by toxicity is not of much concern is supported in this paper. These issues creating obstacles in the path of commercialization of PSCs along with the commercialization road map are discussed thoroughly.